Phytoplankton community succession and cyanobacterial dominance shifts during South-to-North water diversion project: Insights from two impounding reservoirs, China - Shan Jiang; Shasha Zhang; Jielin Wei; Hangzhou Xu; Haiyan Pei (Ecotoxicology and Environmental Safety)
To alleviate local water crises, water diversion projects are carried out in many countries around the world. However, such projects can cause a series of ecological effects with controversial consequences in water-receiving systems. Our study shows the transformations of phytoplankton communities in Datun Reservoir (DT) and Shuangwangcheng Reservoir (SWC), located on the eastern route of the South-to-North Water Diversion Project (SNWDP), China. Phytoplankton communities in these two reservoirs exhibited transient homogenization driven by the complex effects of temperature and water diversion dynamics during the first three years of the study, but ultimately diverged into distinct assemblages after ten years. Further, the newly detected Raphidiopsis raciborskii in later years showed a significant positive correlation with accumulative inflow. Combined with the increase cyanobacterial diversity observed in both reservoirs, these findings indicate that water diversion may be a pathway for cyanobacterial expansion. Moreover, low nitrogen conditions resulting from the water diversion appear to provide a competitive advantageous for nitrogen-fixing cyanobacteria (Raphidiopsis raciborskii and Pseudanabaena limnetica) over non-fixing species (Microcystis aeruginosa). Our study highlights several detrimental ecological issues affecting water-receiving systems, even in the context of improved water quality associated with the SNWDP. It also offers critical insights for managing of water-impounding systems in the future.